2012
DOI: 10.4172/2155-6148.1000244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intraoperative Anesthetic and Fluid Management on 30-day Postoperative Outcomes in a Newly Established Surgical Peritoneal Surface Malignancy Program

Abstract: Background: Anesthetic and fluid management during cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) may influence 30-day postoperative outcomes. We investigated intraoperative management differences and their relation to outcomes in all consecutive patients undergoing HIPEC and CRS following the first 2 years after initiation of this surgical oncology program in a single center. Methods:Following IRB approval we retrospectively recorded demographics, intraoperative anesthetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(33 reference statements)
0
6
0
1
Order By: Relevance
“…The recommended targets for urine output during various phases are up to 0.5 mL/kg/h during CRS, 2–4 mL/kg/h during the HIPEC phase and 1–2 mL/kg/h post-HIPEC phase. [134647] However, these thresholds are debatable in the context of individualised fluid therapy.…”
Section: Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended targets for urine output during various phases are up to 0.5 mL/kg/h during CRS, 2–4 mL/kg/h during the HIPEC phase and 1–2 mL/kg/h post-HIPEC phase. [134647] However, these thresholds are debatable in the context of individualised fluid therapy.…”
Section: Monitoringmentioning
confidence: 99%
“…Fluid overload has been found to be associated with an increased morbidity. [4647] Restrictive fluid regimens have demonstrated decreased perioperative mortality in other major surgical procedures. [626364] However, restricted fluid therapy can cause suboptimal tissue and renal perfusion in the face of extreme haemodynamic changes that occur during the phases of CRS-HIPEC.…”
Section: Monitoringmentioning
confidence: 99%
“…Both hypovolemia and hypervolemia can be detrimental. [ 9 10 ] Urine output measurement could be a noninvasive, reliable surrogate marker of renal perfusion and goal of urine output of 0.5 ml/kg/h during cytoreductive phase; 4 ml/kg/h during HIPEC and 1–2 ml/kg/h in post-HIPEC phase are required. [ 11 ] ABG measurements may guide fluid therapy by lactate levels as well as provide information about acid–base and electrolyte status.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of 34 patients undergoing CRS and HIPEC, authors reported that, in patients with liberal intraoperative fluid replacement, a high postoperative complication rate, especially pulmonary, was observed. [ 14 ] In a recent study on 133 patients, intraoperative fluid rate was significantly associated with increased morbidity. [ 15 ] The patients receiving >15.7 mL/kg/h of intraoperative fluids experienced a 43% increase in complications as compared to those receiving less than this amount.…”
Section: Fluid Managementmentioning
confidence: 99%
“…Meticulous fluid management as per goal-directed therapy appears to answer these issues. [ 13 14 ] The non-invasive cardiac output monitoring and urine output appear to be an acceptable monitoring tool in such surgeries. [ 17 ] The fluid management was guided by non-invasive continuous cardiac output monitoring with FloTrac in patients with high tumour load and patient having persistent haemodynamic perturbations in the study being published.…”
Section: Fluid Managementmentioning
confidence: 99%